Increased concanavalin A induced suppression in treated and untreated coeliac disease. - O'FARRELLY, CLIONA (My University, 1984)
The generation of suppression by concanavalin A in peripheral blood mononuclear cells in treated and untreated coeliac subjects using an in vitro assay was found to be significantly increased when compared with controls. The response of peripheral blood mononuclear cells to the plant mitogen concanavalin A (con A) was also significantly depressed in both groups of coeliac patients. It is proposed that the depressed cell mediated immunity found in this and other studies in coeliac patients is because of increased suppression. The possible connection between these findings and the increased incidence of malignancy also found in coeliac disease is discussed.
PUBLISHED
Keywords: concanavalin A i; concanavalin A i; Immunology, Inflammation & Infection